(untitled) (REMUNOM, 2024)
This article aims to analyze the growing use of social networks by children and adolescents and understand the urgency of specific regulations to protect this age group. The relevance of this research consists of the approach taken on the risks associated with minors’ early access to digital platforms, highlighting the consequences that this use can have on the personal lives of this specific audience and the need to raise awareness among the population regarding this topic. Furthermore, the research presents an analysis of the civil liability of guardians in the face of excessive exposure of minors to social networks, emphasizing the importance of public policies and specific laws that guarantee the safety and privacy of this public when using social networks. Furthermore, the research also takes a legal approach to the principle of vulnerability and its relationship to the protection of minors, as well as proposing guidelines for effective regulation, considering both the rights of children and the responsibilities of platforms and guardians. Furthermore, through the results of the scientific material it is possible to note the gaps in Brazilian legislation in relation to the lack of specific laws on the use of social networks by children and adolescents, highlighting that the development of concrete standards to protect minors in the digital environment would be extremely important. The topic was approached through a hypothetical-deductive method, based on a qualitative approach, using current legislation, doctrinal citations and relevant works on the subject.